2020
DOI: 10.3390/app10176117
|View full text |Cite
|
Sign up to set email alerts
|

Regional Variation and Socio-Economic Determinants of Suicide Mortality in Greece before and during Economic Crisis

Abstract: Background. Suicide mortality increased in Greece after the 2008 financial crisis. This study aimed to explore the regional variation of suicide mortality before and after the economic crisis, and its correlation with socio-economic and mental health-related variables factors. Methods. This is a quasi-experimental ecological study. Data from the national mortality statistics were analyzed, and standardized death rates and age-specific mortality rates were calculated. The effect of economic crisis was explored … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Altogether, 19 studies found increased suicide rates at the level of the total population after the start of the crisis. These were conducted on the populations of Italy (Milan) 116 (suicides as a result of mental and behavioural disorders, Italy 117 ), Greece, 118 – 123 Spain 124 (suicide attempts in Spain 125 ), the European Union, 126 128 Canada, 126 England, 128 130 the USA 131 133 and South Korea. 134 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Altogether, 19 studies found increased suicide rates at the level of the total population after the start of the crisis. These were conducted on the populations of Italy (Milan) 116 (suicides as a result of mental and behavioural disorders, Italy 117 ), Greece, 118 – 123 Spain 124 (suicide attempts in Spain 125 ), the European Union, 126 128 Canada, 126 England, 128 130 the USA 131 133 and South Korea. 134 …”
Section: Resultsmentioning
confidence: 99%
“…Altogether, 19 studies found increased suicide rates at the level of the total population after the start of the crisis. These were conducted on the populations of Italy (Milan) 116 (suicides as a result of mental and behavioural disorders, Italy 117 ), Greece, [118][119][120][121][122][123] Spain 124 (suicide attempts in Spain 125 ), the European Union, [126][127][128] Canada, 126 England, [128][129][130] the USA [131][132][133] and South Korea. 134 Some studies reported increases in suicide rates in specific population subgroups, 135,136 among men [137][138][139] or attributable to specific factors such as unemployment.…”
Section: Affective Disordersmentioning
confidence: 99%
“…Our findings and their implications must be interpreted in the context of study limitations. Similar to other studies (e.g., Harper and Bruckner 2017), we used aggregate, nationwide data to conduct the analysis, which may mask important regional heterogeneity in suicide rates (Zilidis et al 2020) as well as variation in the economic consequences of the debt crisis and austerity measures. Unknown, then, is whether (and to what extent) the debt crisis impacted suicide rates differently in different parts of Greece.…”
Section: Discussionmentioning
confidence: 99%
“…to suicide via deteriorating mental health conditions among the population of Greece, including growing depression, stress, and strain as a result of economic hardship (Zilidis, Papagiannis, and Rachiotis 2020). Mental health depends on a variety of socio-economic and environmental factors (Herrman and Saxena 2005), and financial difficulties can lead to mental health problems (Mucci et al 2016).…”
Section: Economic Crises and Suicide Rates: Theoretical Considerationsmentioning
confidence: 99%
See 1 more Smart Citation